Analysis of Student Misconceptions on the Problem Based Learning (PBL) Model Assisted with Interactive Multimedia on Acid Basic Solutions - Fitriani Mandasari; Irwan Said (Jurnal Akademika Kimia, 2021)
This study aimed to analyze students' misconceptions on Acid-Base Solution after applying the Problem Based Learning (PBL) model assisted with interactive multimedia in grade XI at SMA 4 Palu. This type of research was a quantitative descriptive study with a total sample of 1 class, namely class XI Science-2, with 33 students. The research instrument used was a reasoned multiple-choice test accompanied by a Certainty of Response Index (CRI) consisting of 15 items. The results obtained the average percentage of students' misconceptions in Problem Based Learning (PBL) assisted with interactive multimedia in Acid-Base Solutions before and after the successive application was 42.9% and 21.8%. Thus the application of the PBL model reduced student misconceptions by 21.1%.